Aplication of circular economy to manufacture sneakers from the banana pseudostem yarn - Carcamo Ygnacio, Jayson Jeremy (2025)
Traditional sneaker production uses water and soil contamination, due to the use of synthetic fibers and bad waste management. But new solutions have been developed, one of them being the replacement of natural fiber for synthetic fiber, one of the natural fibers is the banana fiber obtained from the pseudostem using mechanical machinery. The purpose of this article is to prove the feasibility of using mechanical and classical procedures to make sneakers but using banana fiber as the main resource by creating a prototype. The prototype will be tested in a laboratory and have these results: flexural strength with no appreciable damage. The rub fastness result is dry 5 and wet 5. The thickness of the sole is 19.4 mm. The Sole flexural strength does not have signs of damage, and the resistance of the shear-floor joint is 8.9N/mm.